Exploring decision making in social networking for jewelry items - Paramin Chuangemanee (2018)
© 2016 IEEE. Previous studies show that the social networking is effect on our daily life and consumer behavior. It has been rapidly growth in a few year in Thailand. Many kind of product were adopted to selling on social networking. Jewelry is a very interesting and a special characteristic. Furthermore, we found that many brand of jewelry sell directly to customers on social networking sites. This study explore and investigate the factors which influence the purchase decision of jewelry items from social networking by employing value framework theory, which consist of functional values, emotional values, and social values. This findings also have the practical implication as guidance for jewelry sellers to determine the suitable strategy for the jewelry business.